Socioeconomic Predictors of Surgical Resection and Survival for Patients With Osseous Spinal Neoplasms. Issue 3 (April 2019) - Deb, Sayantan; Brewster, Ryan; Pendharkar, Arjun Vivek; Veeravagu, Anand; Ratliff, John; Desai, Atman
Abstract : Summary of Background Data: Primary osseous spinal neoplasms (POSNs) include locally aggressive tumors such as osteosarcoma, chondrosarcoma, Ewing sarcoma, and chordoma. For such tumors, surgical resection is associated with improved survival for patients. Socioeconomic predictors of receiving surgery, however, have not been studied. Objective: To examine the independent effect of race on receiving surgery and survival probability in patients with POSN. Study Design: A total of 1904 patients from the SEER program at the National Cancer Institute database, all diagnosed with POSN of the spinal cord, vertebral column, pelvis, or sacrum from 2003 through 2012 were included in the study. Race was reported as white or nonwhite. Treatment included receiving surgery and no surgery. Materials and Methods: Multivariable logistic regression was used to determine odds of receiving surgery based on race. Survival probability based on and race and surgery status was analyzed by Cox proportional hazards model and Kaplan-Meir curves. Results were adjusted for age at diagnosis, sex, socioeconomic status (composite index), tumor size, and tumor grade. Data were analyzed with SAS version 9.4. Results: The study found that white patients were significantly more likely to receive surgery (odds ratio=3.076, P <0.01). Furthermore, nonwhite race was associated with significantly shorter survival time [hazard ratio (HR)=1.744, P <0.05]. Receiving surgery was associated with improved overall survival (HR=2.486, P <0.01). After adjusting for receiving surgery, white race remained significantly associated with higher survival probability (HR=2.061, P <0.05). Conclusions: This national study of patients with typically aggressive POSN found a significant correlation between race and the likelihood of receiving surgery. The study also found race to be a significant predictor of overall survival, regardless of receiving surgical treatment. These findings suggest an effect of race on receiving treatment and survival in patients with POSN, regardless of socioeconomic status. Further studies are required to understand reasons underlying these findings, and how they may be addressed.